Sentimental analysis of food review contents to improve food culture and the quality of virtual content using natural language processing and machine learning - Sarkar, Ripa; Hassan, Md. Mehedi; Azad, Farin Beante; Hossin, Md. Nibras (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.